Coccidiosis due to Isospora curio (Trachta & Silva et al. 2006) in lesser seed-finches Sporophila angolensis (Linnaeus, 1766) at a commercial breeding facility - Case report - Batista, Lilian C. de S. O.; Vasconcellos, Marcelo dos S. D.; dos Passos, Matheus M.; Lopes, Bruno do B.; Berto, Bruno P. (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Batista L.C. deS.O., Vasconcellos M. dosS.D., dos Passos M.M., Lopes B. doB. & Berto B.P. Coccidiosis due to Isospora curio (Trachta & Silva et al. 2006) in lesser seed-finches Sporophila angolensis (Linnaeus, 1766) at a commercial breeding facility - Case report. [Coccidiose por Isospora curio (Trachta & Silva et al. 2006) (Apicomplexa: Eimeriidae) em Sporophila angolensis (Linnaeus, 1766) numa criação comercial - Relato de caso]. Revista Brasileira de Medicina Veterinária, 37(4):401-405, 2015. Curso de Pós-Graduação em Ciências Veterinárias, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, Campus Seropédica, BR 465 Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: liliancsobatista@hotmail.com Monitoring of a lesser seed-finch breeding is of great importance, for even the clinically healthy animals may be infected. When coccidiosis is diagnosed early, it can often be avoided clinical signs of the disease and the number of deaths in the breeding when associated with hygiene practices in the breeding system. Despite of the low frequency of coccidiosis in the studied passerines, Isospora curio was the unique species found associated with passerines that died in the commercial breeding facility.